Enhancing Disaster and Emergency Preparedness in Schools: An Examination of Management Knowledge and Practices Among Elementary Educators - Manuel, Allyza Ross; Arias, Elpedio; Orfrecio, Marlene; Martinez, Norge; Java, Vinus; Java, Moreno Jr; Janito, Cheeze; Tagare, Ruben Jr (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to assess disaster management knowledge and practices among elementary school teachers in Selected Schools in Cotabato, Philippines, with a focus on preparedness, safety prioritization, and response strategies. Methodology: A quantitative research design was applied using a researcher-made survey questionnaire, validated with Cronbach's alpha values (0.85 and 0.91) to ensure reliability. Simple random sampling, supported by Slovin’s formula, was used to select 70 respondents from five elementary schools, with survey data gathered via school-provided teacher lists. Main Findings: The study found that teachers possess good disaster management knowledge and are prepared with essential supplies but need a stronger focus on personal safety. Awareness is high regarding drought impacts and water conservation, but improvements are needed in early warning systems and device installations. Novelty/Originality of this study: This study provides targeted insights into specific preparedness gaps in school disaster management, especially in early warning and response capabilities. Its findings contribute to disaster readiness by suggesting practical actions that enhance teachers’ skills, align with local needs, and foster community involvement in preparedness efforts.